Accumulation of phenylpropanoids in the rectal glands of males of the Oriental fruit fly,Dacus dorsalis - Nishida, R.; Tan, K. H.; Serit, M.; Lajis, N. H.; Sukari, A. M.; Takahashi, S.; Fukami, H. (Springer Science and Business Media LLC, 1988)
Two phenylpropanoid compounds, 2-allyl-4,5-dimethoxyphenol(II) and coniferyl alcohol(III), were characterized from body tissue of wild males of the Oriental fruit fly,Dacus dorsalis. These compounds accumulated in the rectal glands only when laboratory-reared males were fed with methyl eugenol. Compound II was released into the air during dusk, which coincides with the fly courtship period. Pheromonal and allomonal effects of the phenylpropanoids were examined.